Enhancing activity, nutrition and mental health in overweight adolescents. Stage 1 – Formative research - McManus, Alexandra; Smith, Kyla; Kerr, Deborah; Hunt, Wendy; McManus, Jennifer; Storey, Jessica; White, James; Cuesta-Briand, Beatriz; Straker, Leon (Curtin Health Innovation Research Institute, 2012)
The aim of the project was to refine, implement and evaluate a multi-disciplinary family-centred community-based intervention intended to influence the physical activity, nutrition and psychosocial behaviours of overweight adolescents in Western Australia.